Planning and Executing Aiming Movements in Middle Childhood. Issue 5 (October 2022) - de Oliveira, Danielle S. V.; Alouche, Sandra R.; de Freitas, Sandra M. S. F.; Oba, Gabriela H.; Giangiardi, Vivian F.; de Sá, Cristina dos Santos C.
Harmonious voluntary movements require efficiency in their planning and execution. Throughout middle childhood structural changes in the central nervous and musculoskeletal systems influence these processes and resultant motor behavior. In this study, we evaluated the characteristics of the motor planning and executing of aiming movements directed at targets located in different positions in space in children aged 7, 9, and 11 years. We divided 43 right-handed children, into three age groups and instructed them to perform aiming movements directed at targets using a stylus on a digital tablet. The children performed the movement with their dominant upper limbs from a starting point towards targets positioned ipsilaterally or contralaterally to this dominant limb. We analyzed temporal and spatial variables of motor performance. Younger (7-year-old) children made more errors in the initial movement direction and more frequently corrected their movements during task execution when compared to 9- and 11-year-old children who did not differ from each other. All age groups were similar in movement accuracy and precision. Movements toward contralateral targets were slower and more accurate than movements toward ipsilateral targets for all groups. These results show that performing aiming movements develop with the onset of middle childhood.